Assessing the Effects of Collaborative Professional Learning: Efficacy Shifts in a Three-Year Mathematics Study - Bruce, Catherine D.; Flynn, Tara (Alberta Journal of Educational Research, 2013)
Researchers examine the outcomes of professional collaborative inquiry in mathematics on teacher efficacy in a three-year study of teacher professional learning in Canada. The study applies a mixed methods approach involving over 200 teachers and 1000 students as well as case study sites in English and French. The collaborative inquiry-based professional learning program (called CIL-M) focuses on teacher collaboration, mathematics knowledge for teaching, and student mathematical thinking. The program, which was refined annually based on research report recommendations, was found to increase teacher efficacy, student achievement and positive student beliefs. Les chercheurs ont étudié les résultats d’une enquête collaborative professionnelle en mathématiques portant sur l’efficacité des enseignants et l’apprentissage professionnel du personnel enseignant au Canada. La recherche s’est déroulée sur trois ans, a reposé sur une approche de méthodes mixtes, et a impliqué plus de 200 enseignants, 1 000 étudiants et des sites d’études de cas en anglais et en français. Le programme d’apprentissage professionnel par investigation vise la collaboration entre enseignants, les connaissances de l’enseignement des mathématiques et le raisonnement mathématique chez les élèves. Ce programme a été affiné à chaque année en fonction des recommandations découlant du rapport de recherche. On a trouvé qu’il augmentait l’efficacité des enseignants et améliorait les croyances et le rendement des élèves.